A Chitin-binding Protein Purified from Moringa oleifera Seeds Presents Anticandidal Activity by Increasing Cell Membrane Permeability and Reactive Oxygen Species Production - Neto, João X.S.; Pereira, Mirella L.; Oliveira, Jose T. A.; Rocha-Bezerra, Lady C. B.; Lopes, Tiago D. P.; Costa, Helen P. S.; Sousa, Daniele O. B.; Rocha, Bruno A. M.; Grangeiro, Thalles B.; Freire, José E. C.; Monteiro-Moreira, Ana Cristina O.; Lobo, Marina D. P.; et al. (Frontiers in Microbiology, 2017)
Candida species are opportunistic pathogens that infect immunocompromised and/or immunosuppressed patients, particularly in hospital facilities, that besides representing a significant threat to health increase the risk of mortality. Apart from echinocandins and triazoles, which are well tolerated, most of the antifungal drugs used for candidiasis treatment can cause side effects and lead to the development of resistant strains. A promising alternative to the conventional treatments is the use of plant proteins. M. oleifera Lam. is a plant with valuable medicinal properties, including antimicrobial activity. This work aimed to purify a chitin-binding protein from M. oleifera seeds and to evaluate its antifungal properties against Candida species. The purified protein, named Mo-CBP2, represented about 0.2% of the total seed protein and appeared as a single band on native PAGE. By mass spectrometry, Mo-CBP2 presented 13,309 Da. However, by SDS-PAGE, Mo-CBP2 migrated as a single band with an apparent molecular mass of 23,400 Da. Tricine-SDS-PAGE of Mo-CBP2 under reduced conditions revealed two protein bands with apparent molecular masses of 7,900 and 4,600 Da. Altogether, these results suggest that Mo-CBP2 exists in different oligomeric forms. Moreover, Mo-CBP2 is a basic glycoprotein (pI 10.9) with 4.1% (m/m) sugar and it did not display hemagglutinating and hemolytic activities upon rabbit and human erythrocytes. A comparative analysis of the sequence of triptic peptides from Mo-CBP2 in solution, after LC-ESI-MS/MS, revealed similarity with other M. oleifera proteins, as the 2S albumin Mo-CBP3 and flocculating proteins, and 2S albumins from different species. Mo-CBP2 possesses in vitro antifungal activity against Candida albicans, C. parapsilosis, C. krusei and C. tropicalis, with MIC50 and MIC90 values ranging between 9.45-37.90 µM and 155.84-260.29 µM, respectively. In addition, Mo-CBP2 (18.90 µM) increased the cell membrane permeabilization and reactive oxygen species production in C. albicans and promoted degradation of circular plasmid DNA (pUC18) from Escherichia coli. The data presented in this study highlight the potential use of Mo-CBP2 as an anticandidal agent, based on its ability to inhibit Candida spp. growth with apparently low toxicity on mammalian cells.